Proceedings of the First International Conference on Theoretical, Applied and Experimental Mechanics - Gdoutos, Emmanuel E.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
ICTAEM_1 treated all aspects of theoretical, applied and experimental mechanics including biomechanics, composite materials, computational mechanics, constitutive modeling of materials, dynamics, elasticity, experimental mechanics, fracture, mechanical properties of materials, micromechanics, nanomechanics, plasticity, stress analysis, structures, wave propagation. During the conference special symposia covering major areas of research activity organized by members of the Scientific Advisory Board took place. ICTAEM_1 brought together the most outstanding world leaders and gave attendees the opportunity to get acquainted with the latest developments in the area of mechanics. ICTAEM_1 is a forum of university, industry and government interaction and serves in the exchange of ideas in an area of utmost scientific and technological importance.
Influence of Sample Preparation on Determined Nanomechanical Properties of Metastable Calcium Carbonate Polymorphs -- Crystallization and Dissolution of Common Salts - Damage Potential to Porous Media -- Torsional shear testing of mortar -- Comparative tests of strengthening effects on weak mortars consolidated with various agents -- Novel Device for 4-point Flexural Testing of Quasi-brittle Materials during 4D Computed Tomography -- Effects of Long-term Aging on the Low-cycle Fatigue Behavior of Inconel 718 superalloy -- Enhanced Young's modulus in percolative cementitious composites reinforced with carbon nanotubes -- Behavior of Partially and Fully FRP-Confined Circularized Square Columns (CSCs) under Axial Compression -- Stress-Strain Behavior of Circular Concrete Columns Partially Wrapped with FRP Strips -- Improving the Tribological Properties of Ti6Al4V Alloy with Multi-Walled Carbon Nanotube Additions.
Keywords: Mechanics, Applied; Solids; Solid Mechanics